Sensation seeking, Self-esteem and Sexting in University Students of Metropolitan Lima - Muñoz, Gianella (2024)
Introduction: The use of social networks can trigger addictive behaviors in some cases, as well as influence the development of other risk behaviors such as sexting; Objective: relate sensation seeking, self-esteem and sexting in university students from Metropolitan Lima. Method: 151 young people and adults (59.5% women) from 18 to 30 years old participated (M= 21.8; DE= 3.09), they were administered the Sensation Seeking Scale, the Rosenberg Self-Esteem Scale and the Sexting Behavior Scale. Results: Moderate significant correlations were found between sensation seeking with the total sexting score and its dimensions: active disposition towards sexting and actual participation in sexting, not so with the dimension emotional expression in which a weak non-siognificant relationship is found; likewise, sensation seeking and sexting reach very low levels of significance in their relationship with self-esteem; When comparing the variables by sex, no differences were found with any of the variables, and, comparing them by the tipe of relationship they have, it was found that those who say they practice casual sex have signiticantly higher sscores only in the total sexting score and its dimensions active disposition towards sexting and actual participation in sexting. Conclusion: the sexting practice is related to the search for sensations, especially in active towards sexting and real participation in sexting, but not in the emotional expression dimension of sexting.